POTENSI EKSTRAK KULIT BATANG Rhizophora mucronata SEBAGAI ANTIBAKTERI UNTUK MENANGGULANGI SERANGAN BAKTERI Aeromonas hydrophila PADA BENIH IKAN GURAMI (Osphronemus gouramy) - Ellizabet Nababan; Dwi Suryanto; Febrina Arli (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Motile Aeromonas Septicaema (MAS) disease is a bacterial disease effecting of gurami fish of culture, seeds and adults. One alternative to prevent the disease is to use extract of plant. This study aimed to know the effectiveness of R.mucronata bark extract in decresing MAS in gurami seeds in vitro and in vivo, and to determine its LC50 in the fish. Extraction of the bark was done using solvents such as methanol, ethyl acetate and n-heksane. LC50 assay of the extract was done to gurami seeds for 48 hours. The extract was assayed to gurami seeds to know the fish tolerance. Assay on ability of the extract to decrease A.hydrophila growth was conducted, by dropping the extracts on disc blanc and putting the disc into the bacterial lawn. The result showed the extract methanol of the bark was more effective in inhibiting grow of A.hydrophila, however its ability in reducing the disease was least. LC50 of the methanol was in 62,6 ppm.Keywords: Aeromonas hydrophila, antimicrobial activity, Rhizophora mucronata, Seeds Gurami